Empowering people to protect environment: A case study of PT. Indaco Warna Dunia’s CSR - Hilmi Pujihartati Sri (EDP Sciences, 2021)
Corporate social responsibility is a company obligation to be responsible on the social atmosphere besides being able to improve the company's image. In addition to corporate benefits, CSR can contribute to environmental-based participatory community empowerment. This paper explores the environmental empowerment carried out by the CSR of PT. Indaco Warna Dunia that collaborates with the surrounding community. This research uses a case study approach. Data collection was carried out by observation, in-depth interviews, and literature study. The results showed that the empowerment does many empowering and sustainable act to save environment. The programs are reforestation, environmental education through festivities, applying green concept in a building, hydroponic education, garbage bank, and etc. The contribution felt by the community is considered real and beneficial in a sustainable manner. The CSR uses unique strategy to empower people to protect environment in creative manners.